Antagonism of Eucalyptus endophytic fungi against some important crop fungal diseases - Aleahmad, Parmida; Ebrahimi, Leila; Safaie, Naser; Etebarian, Hassan Reza (Frontiers in Microbiology, 2025)
Endophytic fungi colonize plants without causing symptoms, throughout or at least a significant part of their life cycle, forming a plant-fungal association. In this study, endophytic fungi were isolated from Eucalyptus camaldulensis trees, and their antifungal activity was evaluated against four significant plant pathogens namely Botrytis cinerea, Fusarium oxysporum f. sp. lycopersici, Macrophomina phaseolina, and Rhizoctonia solani. For this aim, 754 fungal isolates were obtained from 44 healthy fruit, leaf, and branch samples collected from five provinces of Iran. Subsequently, 27 fungal genera were identified based on morphological characteristics and molecular data of ITS region, with Neofusicoccum, Cladosporium, Didymosphaeria, and Chaetomium being the most commonly found genera. Based on the morphological characteristics, 170 isolates were chosen and their antifungal activities were assessed against the aforementioned pathogens in vitro through dual culture and volatile organic compounds (VOCs) tests. Based on the results, five isolates comprising Trichoderma sp. KL1, Trichoderma sp. 8S1, Chaetomium sp. DL4, Phaeophleospora sp. XL4, and Pseudosydowia sp. VL3 were selected for further investigation, which included examining their chitinase and cellulase secretion capabilities as potential antagonism mechanisms and their ability to solubilize phosphate as a growth-promoting mechanism. Furthermore, the antifungal activity of the selected isolates was evaluated against plant pathogens on tomato plants under greenhouse conditions. Their impact on plant growth parameters was also assessed. In vitro and greenhouse experiments demonstrated that each selected isolate exhibited varying levels of control against different pathogens. Among the isolates, Trichoderma sp. isolates KL1 and 8S1 consistently exhibited the strongest inhibition of disease severity for all four pathogens under greenhouse conditions. Lastly, the selected isolates were identified as Trichoderma longibrachiatum KL1, T. longibrachiatum 8S1, Chaetomium globosum DL4, Phaeophleospora eucalypticola XL4, and Pseudosydowia eucalypti VL3 based on their morphological features and molecular data of the ITS1-5.8S-ITS2 and tef-1α genomic regions.